Pharmacokinetics and Safety of Single-Dose Amphotericin B Colloidal Dispersion in Healthy Chinese Subjects and Population Pharmacokinetic/Pharmacodynamic Analysis to Inform Clinical Efficacy in Invasive Infections Caused by Candida albicans - Huang, Zhi-Wei; Yu, Ji-Cheng; Wang, Jing-Jing; Chen, Yuan-Cheng; Wu, Ju-Fang; Chen, Yi-Jian; Cao, Guo-Ying; Yang, Hai-Jing; He, Jin-Jie; Dai, Jing-Yi; Zhang, Ji-Yin; Zhang, Wei; et al. (Clinical therapeutics, 2021)
•Three doses of amphotericin B colloidal dispersion (ABCD) (0.5, 1.0, and 1.5 mg/kg) were well tolerated in the healthy Chinese subjects, and the plasma concentrations fitted a three-compartment model of PK.•PPK modeling extrapolated the exposure of standard dose (3 and 4 mg/kg) ABCD in patients.•PK/PD analysis and Monte Carlo simulations predicted that 3 or 4 mg/kg qd for 14-28 days after intravenous injection of ABCD will be efficacious against IFIs caused by C. albicans with an MIC≤2 or 4 mg/L (PTA>90% and CFR>98%). Amphotericin B colloidal dispersion (ABCD) is a less toxic formulation of amphotericin B for the treatment of invasive fungal infections. The pharmacokinetic (PK) profile and safety of a generic ABCD were investigated after a single dose (0.5 to 1.5 mg/kg) administered as an intravenous infusion in 30 healthy Chinese subjects. PK data from healthy Chinese male subjects were applied for developing a population PK model to predict the PK profiles of standard doses (3 or 4 mg/kg) in patients. A 5000-time Monte Carlo simulation of AUC0–24/MIC target was implemented to determine the probability of target attainment (PTA) and cumulative fraction of response (CFR) under standard doses. The PK profiles of intravenous administration of ABCD were best described by a 3-compartmental model with a time-varying clearance and a dose-dependent volume of distribution in the peripheral compartment. PK/pharmacodynamic (PK/PD) analysis revealed that 3 or 4 mg/kg ABCD once a day resulted in favorable CRF (>98%) with 2-log reduction of Candida albicans. A high PTA (>90%) was achieved at MIC ≤2 mg/L for the dosing regimen of ABCD 3 mg/kg and 4 mg/kg for MIC ≤4 mg/L. PK/PD analysis indicated that a favorable efficacy of ABCD could be reached at a dose of 3 or 4 mg/kg once daily for 14 to 28 days to treat invasive fungal infections caused by C albicans. ClinicalTrials.gov identifier: NCT03577509.